2013
DOI: 10.4021/jocmr1227w
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Trauma Patients With Cervical Spine Fractures due to Ground Level Fall: Five Years Experience in a Level One Trauma Center

Abstract: BackgroundIt has been found that significantly different clinical outcomes occur in trauma patients with different mechanisms of injury. Ground level falls (GLF) are usually considered “minor trauma” with less injury occurred in general. However, it is not uncommon that geriatric trauma patients sustain cervical spine (C-spine) fractures with other associated injuries due to GLF or less. The aim of this study is to determine the injury patterns and the roles of clinical risk factors in these geriatric trauma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
1
24
0
3
Order By: Relevance
“…Organ damage, which is a risk factor for mortality from blunt injury, has been the subject of numerous previous studies, and intracranial hemorrhagic lesions, cervical spinal cord damage, hemothorax, pneumothorax, intra-abdominal organ injury, and leg fractures have been reported to constitute independent risk factors for mortality [2,5,7,14,[21][22][23]. Studies of ground-level falls have also identified high AIS in the head, thoracic, abdominal, pelvic, and leg areas in cases of death [5].…”
Section: Discussionmentioning
confidence: 93%
“…Organ damage, which is a risk factor for mortality from blunt injury, has been the subject of numerous previous studies, and intracranial hemorrhagic lesions, cervical spinal cord damage, hemothorax, pneumothorax, intra-abdominal organ injury, and leg fractures have been reported to constitute independent risk factors for mortality [2,5,7,14,[21][22][23]. Studies of ground-level falls have also identified high AIS in the head, thoracic, abdominal, pelvic, and leg areas in cases of death [5].…”
Section: Discussionmentioning
confidence: 93%
“…In a large retrospective observational study of 12 805 trauma patients, Wang et al . reported that the majority (54.0%) of cervical spine fractures in the elderly were due to falls, whereas, in the non‐geriatric group, transport‐associated accidents accounted for 79.6% of cervical spine fractures …”
Section: Discussionmentioning
confidence: 99%
“…20 Older patients are also more likely to sustain cervical spine injuries that are clinically unstable, involve more than one vertebral level and occur in the upper cervical spine. 20 The distribution of mechanism of injury also varies between older and younger patients. In a large retrospective observational study of 12 805 trauma patients, Wang et al reported that the majority (54.0%) of cervical spine fractures in the elderly were due to falls, whereas, in the non-geriatric group, transport-associated accidents accounted for 79.6% of cervical spine fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 One possible explanation is that, because hip fracture is so much more common than cervical fracture after low-impact falls, fall prevention and treatment for osteoporosis may shift the age-specific incidence of hip fracture toward the oldest adults, who are more likely to be women. 18 Not surprisingly, head injury is closely associated with cervical spinal injury, 19 leading to higher ISS in individuals with cervical fracture with and without SCI. After accounting for these differences between groups using propensity score modeling, it was found that, despite being younger, having fewer comorbid illnesses, and being more likely to receive care at teaching hospitals and higher-level trauma hospitals, Medicare beneficiaries who sustained a cervical fracture after a low-impact fall were nearly twice as likely to die within 30 days of their injury as those who sustained a hip fracture.…”
Section: Discussionmentioning
confidence: 99%